PENGEMBANGAN MEDIA “SERUNYA BELAJAR ORGAN GERAK HEWAN DAN MANUSIA” BERBASIS POWERPOINT DI KELAS V SEKOLAH DASAR - Rezan Rezan; Dian Nuzulia Armiena; Sylvia Lara Syaflin (Universitas Sarjanawiyata Tamansiswa, 2023)
This researcher aims to produce (1) validation results for powerpoint media products which in terms of media, material and language obtained an average of 88.9% in the